Qualidade de vida e adaptação de pessoas colostomizadas antes e após o uso do oclusor - Diniz, Iraktania Vitorino (2021)
Patients with intestinal ostomies have to deal with many challenges related to changes in their quality of life and their adaptation. Aim: To analyze the quality of life and adaptation of colostomized patients that use the occluder. Methods: organized in three steps, these being a methodological study towards the formulation and validation of an educational booklet about the use of the occluder; an intervention study based on training focused on the use of the occluder and on the assessment of the patient’s adaptation and quality of life; and a qualitative study in order to understand the perceptions and adaptative feelings of colostomized patients before and after the use of the occluder. The study was conducted in the Ostomy Reference Center. Among the 26 eligible patients to enter the study, the final sample included 19 of these patients. The three following tools were applied: a sociodemographic and clinical tool - the City of Hope-Quality of Life-Ostomy Questionnaire and the adaptation scale of ostomized patients. The Content Validity Index (CVI) was also applied so as to assess the concordance rate of the evaluators. Descriptive and inferential statistics were employed, and for the sake of comparisons before and after the use of the occluder, the paired T test and the Pearson's correlation test were also used. The qualitative data were transcribed and organized into a corpus and processed with the aid of a Textual Analysis software. The project was approved by the Ethics Committee of the Health Sciences Center of the Federal University of Paraiba. Results: The mean age was 55,9 (range: 41-79 years) and standard deviation 9,53. Most patients were females, married and retired, 31,6% have a secondary education diploma, 52,6% have a family income of up to three minimum wages. The methodological study resulted in the production of the educational booklet with the following overall content validity index: 0,99 by experts and 0,94 by colostomized patients. In the intervention study, results pointed to a better quality of life and better adaptation scores of patients after the use of the occluder. The findings also confirmed strong, positive and significant correlations between adaptation and quality of life. The qualitative study before the occluder gave rise to four modes with three connecting points and, after the use of the occluder, three modes with two connecting points rose up, these being categorized in the light of Callista Roy’s adaptation model. The colostomy occluder is, therefore, a favorable instrument to the adaptation and quality of life. Besides that, it is a valuable resource to health professionals, especially those in the nursing field, contributing also to a shift in the care paradigm, with a focus on devices that promote continence.